“C’est un amour ou Cupidon nouveau”: Spiritual Passion and the Profane Persona in Anne de Marquets’s Les Divines Poesies de Marc Antoine Flaminius (1568–1569) - MacAskill, Annick (Renaissance and Reformation / Renaissance et Réforme, 2015)
While best known for her 480 Sonets spirituels, published seventeen years after her death in 1605, the Dominican nun Anne de Marquets also contributed a remarkable collection of personal spiritual poetry during her lifetime in Les Divines Poesies de Marc Antoine Flaminius (Paris, chez N. Chesneau, 1568; reedited in 1569). In the pages following her translation of Marcantonio Flaminio’s Carminum sacrorum libellus, her original cantiques ou chansons spirituelles and sonets de l’amour divin reveal a convergence of Renaissance poetics and traditional Christian themes. In particular, Anne de Marquets looks to the Petrarchan tradition as a model for the expression of her love for the divine. Drawing on images and themes from Petrarch and his earliest French imitators, the Dominican adopts the poetic process promoted by the Pléiade, notably in Du Bellay’s Deffence et Illustration de la langue françoyse and in Ronsard’s ode Hercule chrestien.